Confidence Level and Ability of Medical Students to Identify Abdominal Structures After Integrated Ultrasound Sessions - Nausheen, Fauzia; Young, Corey; Brazil, John; Dunagan, Timothy; Bhupathy, Renu; Elango, Sambandam; Crowley, Jason (Ultrasound International Open, 2020)
Determine the confidence level and ability of first year medical students to identify abdominal structures using a wireless portable ultrasound scanner.The students were assessed for their confidence and ability to perform abdominal ultrasound. The 5-point Likert survey included questions on their perception about ultrasound as a resource for learning anatomy, physical examination skills, and the quality of the pre-session instructions. Data was also recorded by the faculty about the students’ ultrasound skills and confidence. Goodman and Kruskal's gamma was used to demonstrate an association between the students’ ability to identify the structures and the self-reported student confidence level. Most of the students had confidence and were able to identify the liver, kidney, and urinary bladder, while almost half of them needed faculty help them to identify the inferior vena cava and aorta. The spleen and gall bladder were the most difficult to locate even for the very confident students. The perception of supervising faculty was that the confidence level was low in most of the students and only 13–20% of students felt “very confident” about performing ultrasound. Almost 37% needed encouragement and support and almost 10% of the students were not willing to try to locate difficult organs. Some students started locating the ureteric jet and portal vein. Most of the students agreed that ultrasound is an excellent resource for learning anatomy and physical examination skills. All students suggested having more ultrasound sessions. Most of the students feel confident about performing ultrasound and they perceive that ultrasound can enhance their basic sciences and physical examination skills.
Keywords: medical education; anatomy; physical examination skills; ultrasound; curriculum